Effect of testing experience and profession on provider acceptability of rapid HIV testing after implementation in public sexual health clinics in Sydney1. Issue 5 (21st January 2015) - Conway, DP; Guy, R; McNulty, A; Couldwell, DL; Davies, SC; Smith, DE; Keen, P; Cunningham, P; Holt, M; Sydney Rapid HIV Test Study
<x xml:space="preserve">Abstract</x> Objectives Rapid HIV testing (RHT) is well established in many countries, but it is new in Australia since a policy change in 2011. We assessed service provider acceptability of RHT before and after its implementation in four Sydney public sexual health clinics. Methods Service providers were surveyed immediately after training in RHT and again 6–12 months later. Differences in mean scores between survey rounds were assessed via t‐tests, with stratification by profession and the number of tests performed. Results RHT was rated as highly acceptable among staff at baseline and acceptability scores improved between survey rounds. Belief in being sufficiently skilled and experienced to perform RHT (P = 0.004) and confidence in the delivery of nonreactive results increased (P = 0.007), while the belief that RHT was disruptive declined (P = 0.001). Acceptability was higher for staff who had performed a greater number of tests regarding comfort with their role in RHT (P = 0.004) and belief that patients were satisfied with RHT (P = 0.007). Compared with nurses, doctors had a stronger preference for a faster rapid test (P = 0.027) and were more likely to agree that RHT interfered with consultations (P = 0.014). Conclusions Differences in responses between professions may reflect differences in staff roles, the type of patients seen by staff and the model of testing used, all of which may affect the number of tests performed by staff. These findings may inform planning for how best to implement RHT in clinical services.